1992
DOI: 10.1073/pnas.89.10.4319
|View full text |Cite
|
Sign up to set email alerts
|

Golgi retention of a trans-Golgi membrane protein, galactosyltransferase, requires cysteine and histidine residues within the membrane-anchoring domain.

Abstract: Galactosyltransferase (GT; UDPgalactose:beta-D-N-acetylglucosaminide beta-1,4-galactosyltransferase, EC 2.4.1.22) is a type II membrane-anchored protein composed of a short N-terminal cytoplasmic tail, a signal/membrane-anchoring domain, and a stem region followed by a large catalytic domain including the C terminus. To identify the peptide segment and key amino acid residues that are critical for Golgi localization of GT, the expression vector pGT-hCG was designed to encode the entire GT molecule fused to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(82 citation statements)
references
References 33 publications
3
78
1
Order By: Relevance
“…However, these GalT I dimers, which appear to constitute less than one half of the total enzyme, are quite resistant to standard reducing conditions, suggesting that dimerization may not necessarily involve a disulfide bond (28). Intriguingly, previous work by Aoki et al (30) showed that the replacement of this Cys and His residue in the GalT I transmembrane domain increased cell surface expression of the GalT I. Analysis of the C24A mutant that eliminates the dimerization of the STtyr isoform suggests that dimerization of this form of the enzyme does not significantly alter its exit from the Golgi, as measured by its cleavage and secretion (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…However, these GalT I dimers, which appear to constitute less than one half of the total enzyme, are quite resistant to standard reducing conditions, suggesting that dimerization may not necessarily involve a disulfide bond (28). Intriguingly, previous work by Aoki et al (30) showed that the replacement of this Cys and His residue in the GalT I transmembrane domain increased cell surface expression of the GalT I. Analysis of the C24A mutant that eliminates the dimerization of the STtyr isoform suggests that dimerization of this form of the enzyme does not significantly alter its exit from the Golgi, as measured by its cleavage and secretion (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…These act to keep proteins in the Golgi and, so far, all Golgi proteins (Machamer and Swift, 1991) and enzymes (Nilsson et al, 1991;Munro, 1991;Aoki et al, 1992;Burke et al, 1992;Colley et al, 1992;Tang et ai., 1992;Teasdale et al, 1992;Wong et al, 1992) have been found to be retained by the membrane-spanning domain. The mechanism of retention is still unclear though two possibilities have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Golgi retention signals were first identified in a viral protein (Swift and Machamer, 1991) and in Golgi glycosylation enzymes (Nilsson et al, 1991;Munro, 1991;Aoki et al, 1992;Burke et al, 1992;Colley et al, 1992;Tang et al, 1992;Teasdale et al, 1992;Wong et al, 1992). In all cases, the retention signal lies in the membrane-spanning domain.…”
mentioning
confidence: 99%
“…Other reports assign importance to the TMD for localization of glycosyltransferases (GTs) in the Golgi (Opat et al, 2001;Tang et al, 1992;Teasdale et al, 1992). This capacity was attributed to particular amino acid residues in the TMD (Aoki et al, 1992;Sousa et al, 2003) or the length of the TMD (Bretscher and Munro, 1993;Rayner and Pelham, 1997;Ronchi et al, 2008). Recent analyses of a large protein dataset showed that TMDs from single-spanning membrane proteins of the Golgi and plasma membrane have distinctive geometric features: Golgi protein TMDs are on average four amino acid residues shorter than those of plasma membrane proteins in vertebrates, and seven residues shorter in fungi.…”
Section: Introductionmentioning
confidence: 99%